The Communication Strategies Used by Billfath English Students: Tarone’s Taxonomy: The Communication Strategies Used by Billfath English Students: Tarone’s Taxonomy - Rajid Kurniawan; Ahmad muhyidin; M. Labib Al Halim (JEET, Journal of English Education and Technology, 2022)
Communication strategy is a mutual attempt in the communication between two interlocutors to make a deal on an importance communication. We realize that both speaker and the listener are included; the responsibility of both speaker and listener is successful communication. This study aims to identify the types of communication strategies used by eighth grade students of Billfath English students. And this research tried to find out the most dominant communication strategies used by English language education students at Billfath University. The researcher used communication strategies from Tarone’s taxonomy to cultivate the data. This research is a qualitative descriptive. The researcher took 10 students as sample. The techniques used by the researcher to collect data are observation, interviews, and documentation analysis. The data was analyzed with communication strategy from Tarone’s taxonomy. The results of this study indicate that there are 5 types of communication strategies used by English students in order to deal with their difficulties in speaking. The researcher found 75 data of communication strategies used by the English students. The students used topic avoidance 8 data (10,6%),the use of paraphrase 6(8%),native language switching 19 data (25,3%), miming 29 data (38,8%) appeal for assistance 13 data (17,3%). And in this research, the English students did not use coinage and message abandonment. The most dominant strategy used by students is Miming 29 data (38.8%). Communication strategies were used by English students because they tried to overcome communication barriers when they were speaking.